A Conceptual Analysis of Conceptual Analysis in Analytic Jurisprudence. Issue 2 (1st August 2017) - Zanghellini, Aleardo
Abstract : Conceptual analysis remains the methodology of much contemporary mainstream jurisprudence. The last fifteen years have seen significant contributions addressing the nature of conceptual analysis in legal theory, but many questions have not been answered in a satisfactory way. These questions can be more clearly addressed if we appreciate: a) that there is a central case of conceptual analysis; and b) the ways in which non-paradigmatic cases of conceptual analysis differ from the central one. Among other things, the article argues that conceptual analysis is necessary but not sufficient to a full understanding of the nature of law. Some knowledge about law is impervious to conceptual analysis but not to empirical social science. The reverse is also true. In explaining the meaning of 'conceptual analysis' the article also enacts conceptual analysis: the method the article uses to clarify the nature of conceptual analysis is precisely the method known as 'conceptual analysis'.